Rating funduszy inwestycyjnych - proces przyznawania, skale - Krawiec, Wojciech (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The integral part of finance market is existence of specialized agencies, which are responsible for evaluating the securities and their issuer's. Also mutual fund and the fund management are rated by rating agencies. During this process many factors are took into consideration, such as: credit quality, liquidity, portfolio weighted average maturity, diversification, investment policies, risk management policies, organizational structure, quality of human resources, information systems and internal control.The most often the worldwide rating agencies assign a money market fund rating, a bond fund credit quality rating (bonds fund also assigned a bond fund volatility rating) and management quality rating. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 288-295